2013
DOI: 10.1016/j.destud.2012.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Using eco-design tools: An overview of experts' practices

Abstract: International audienceThe practice of eco-design requires relating traditional design criteria to new environmental criteria. So far, few studies have investigated the nature and singularities of eco-design. This article provides some elements of response based upon the redesign of a consumer product (disposable razor). The study was conducted by three groups of experienced eco-designers using existing eco-design tools (SIMAPRO, ECOFAIRE, ECODESIGN PILOT). A protocol analysis with a three-level coding of trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(64 citation statements)
references
References 25 publications
0
62
0
2
Order By: Relevance
“…La fabricación de prendas de punto con la técnica tradicional de "prendas menguadas" (fully fashioned en terminología anglosajona), hace que el desperdicio de fibras sea prácticamente nulo, frente a la confección de tejidos de calada confeccionados por corte y cosido que generan un desperdicio de tejido de entre un 50% a un 17% (Sissons, 2010) (figura 10). Como indican Vallet y Eynard, para encontrar soluciones de diseño centradas en el eco-diseño, uno de los factores principales en la estrategia frente al impacto ambiental es la reducción del uso de materias primas (Vallet et al, 2013). Por tanto, el diseño y fabricación de prendas con la técnica aportada por las tricotosas permite actuar de raíz eliminando residuos y ahorrando materiales, siendo así una técnica dentro de los parámetros de diseño sostenible.…”
Section: Resultsunclassified
“…La fabricación de prendas de punto con la técnica tradicional de "prendas menguadas" (fully fashioned en terminología anglosajona), hace que el desperdicio de fibras sea prácticamente nulo, frente a la confección de tejidos de calada confeccionados por corte y cosido que generan un desperdicio de tejido de entre un 50% a un 17% (Sissons, 2010) (figura 10). Como indican Vallet y Eynard, para encontrar soluciones de diseño centradas en el eco-diseño, uno de los factores principales en la estrategia frente al impacto ambiental es la reducción del uso de materias primas (Vallet et al, 2013). Por tanto, el diseño y fabricación de prendas con la técnica aportada por las tricotosas permite actuar de raíz eliminando residuos y ahorrando materiales, siendo así una técnica dentro de los parámetros de diseño sostenible.…”
Section: Resultsunclassified
“…A quick analysis using standard MFA-based Ecodesign methodology [8] has shown that the recycling rates calculated for the five designs using such an approach is significantly higher than that estimated by the methodology in this paper. It is obvious that this produces no tangible design improvement suggestions to the design engineer.…”
Section: Application Of the Five Fundamental Dfr Rules To Led Designmentioning
confidence: 94%
“…Linking the product designer and metallurgical processing as shown in Fig. 1 is hardly possible with the simplified approaches being suggested and discussed by Vallet et al [8], Karlsson and Luttropp [9], Luttropp and Lagerstedt [4], and Bonvoisin et al [10]. Predicting the recovery of the multitude of elements from complex products shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the designer's expertise in sustainable design is more influential than sustainable design tools in defining environmental assessment and strategy [12].…”
Section: What Is Sustainable Design?mentioning
confidence: 99%